2013
DOI: 10.1080/17512786.2013.813194
|View full text |Cite
|
Sign up to set email alerts
|

Virtuous or Vitriolic

Abstract: In an effort to encourage community dialogue while also building reader loyalty, online newspapers have offered a way for readers to become engaged in the news process, most popularly with online reader comment boards. It is here that readers post their opinion following an online news story, and however much community interaction taking place therein, one thing appears evident: sometimes the comments are civil; sometimes they are not. Indeed, one of the chief defining characteristics of these boards has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(168 citation statements)
references
References 26 publications
1
144
1
7
Order By: Relevance
“…Our results reveal that anonymity (on its own) did not affect the use of aggressive expressions in online comments: There was no difference between participants who had commented with the anonymous WordPress guest account and participants who had used their Facebook account. Based on deindividuation theory (Festinger et al, 1952) and research on incivility in online discussions (Santana, 2014), we had expected anonymity to be a driving factor for verbal aggression in online comments. The method of this study could be one reason for not finding any effects of anonymity because, other than most studies in the field of online aggression, we used a controlled experimental design and did not analyze existing data from web forums or online discussion groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results reveal that anonymity (on its own) did not affect the use of aggressive expressions in online comments: There was no difference between participants who had commented with the anonymous WordPress guest account and participants who had used their Facebook account. Based on deindividuation theory (Festinger et al, 1952) and research on incivility in online discussions (Santana, 2014), we had expected anonymity to be a driving factor for verbal aggression in online comments. The method of this study could be one reason for not finding any effects of anonymity because, other than most studies in the field of online aggression, we used a controlled experimental design and did not analyze existing data from web forums or online discussion groups.…”
Section: Discussionmentioning
confidence: 99%
“…And indeed, empirical research has shown that anonymity seems to affect the use of incivility in online commenting spaces: Comparing user comments from online newspaper forums that allow anonymity with those on news sites that require users to register by real name or to log in with their Facebook account, Santana (2014) found more incivility in anonymous comments. Similarly, Rowe (2015) conducted a comparative content analysis of user comments posted on the Washington Post website or the Washington Post Facebook page and found that the amount of incivility was higher in website comments than in Facebook comments, especially with regard to interpersonal aggression.…”
Section: Anonymity Deindividuation and Aggressionmentioning
confidence: 99%
“…While some studies show that anonymity might have a negative impact on civility (Coleman and Moss 2012;Santana 2014), others indicate that the topic discussed also plays an important part (Berg 2016). The ideals for online debate differ within particular traditions.…”
Section: Editorial Control In Online Comment Fields 365mentioning
confidence: 99%
“…Scholars have pointed towards several challenges with online discussion formats like the rise of echo chambers and polarization of opinions (Sunstein 2007), "flaming" (e.g. Hutchens, Cicchirillo, and Hmielowski 2015;Lee 2005;Santana 2014), "trolling" (e.g. Binns 2012;Hardaker 2010) and harassment of women (e.g.…”
Section: Ambivalence Towards Comment Fieldsmentioning
confidence: 99%
“…For a comprehensive overview of the performativity of hate speech, see Leezenberg (2015). 2 For the role of anonymity in encouraging incivility among Internet users, see Santana (2014); for the interface between anonymity, accountability for one's words and tendency towards mental shortcuts and simplistic judgements, see Tetlock (1983).…”
Section: Youth and Hate Speech In The (Mediatised)mentioning
confidence: 99%